FYR Macedonia Workforce Development : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
Since its independence in 1991, FYR Macedonia has faced a number of challenges in its political and economic transition. One of the greatest has been the shift from a planned economy to a free market oriented economy. This shift resulted in an average annual GDP growth rate of 0.2 percent between 1990 and 2006. Since then, the economy has embarked on an ambitious reform agenda, which has resulted in an average real annual GDP growth of 3.4 percent. The government’s objective is to steer Macedonia toward economic activities with higher value-added and technological content. Strengthening policies for the development of human resources is crucial for the future of the country. A huge challenge in this process is the set-up of an effective and efficient system for workforce development (WfD), one that provides future workers with the skills needed in a modern labor market, enhances the adaptability of those workers who have lost or are at risk of losing their jobs, and prepares the current and future workforce for mobility in work and learning. The rest of this report summarizes the key findings of the SABER-WfD assessment in Macedonia and also presents the detailed results for each of the three functional dimensions. To put the results into context, the next section offers a brief profile of the country’s socioeconomic makeup.